Effect of Farmers’ Multidimensional Beliefs on Adoption of Biofortified Crops Evidence from Sweetpotato Farmers in Tanzania - Shikuku, Kelvin Mashisia; Okello, J.J.; Sindi, K.; Low, Jan W.; McEwan, M. (Informa UK Limited, 2017)
We examined the effect of multidimensional farmers’ beliefs on the likelihood of cultivating planting materials of biofortified orange-fleshed sweetpotato (OFSP) varieties. Using a panel dataset and combining difference-in-differences regression with propensity score matching, results showed positive effects of beliefs related to health benefits, yielding ability, sweetness, disease-resistance, storability, early maturity, colour, and that children enjoy eating OFSP roots, on cultivation of OFSP varieties. The proportion of OFSP roots out of total sweetpotato production for a household increased among farmers’ who held these beliefs. Efforts to promote biofortified crops can, therefore, benefit from taking farmers’ multidimensional beliefs into consideration.